Acceleration of the gastrointestinal transit by polyethylene glycol effectively treats unconjugated hyperbilirubinaemia in Gunn rats. Issue 3 (5th November 2009) - Cuperus, Frans J C; Iemhoff, Arjan A; van der Wulp, Mariette; Havinga, Rick; Verkade, Henkjan J
Abstract : Background and aims: Several conditions that delay gastrointestinal transit are associated with unconjugated hyperbilirubinaemia. We hypothesised that the gastrointestinal transit time is directly related to plasma unconjugated bilirubin (UCB) concentrations, and that this relationship can be used to develop a new therapeutic strategy for severe unconjugated hyperbilirubinaemia in the Gunn rat model. Methods: Gunn rats received, for various time periods, oral polyethylene glycol (PEG) with or without conventional phototherapy treatment to accelerate, or oral loperamide to delay gastrointestinal transit. Gastrointestinal transit time and UCB concentrations in plasma, faeces, intestinal content and bile were determined. Results: Within 36 h, PEG administration accelerated gastrointestinal transit by 45% and simultaneously decreased plasma UCB concentrations by 23% (each p<0.001). The decrease in plasma UCB coincided with an increased small intestinal UCB content (+340%, p<0.05) and an increased faecal UCB excretion (+153%, p<0.05). After 2 weeks, PEG decreased plasma UCB by 41% as single treatment, and by 62% if combined with phototherapy (each p<0.001). Loperamide delayed gastrointestinal transit by 57% and increased plasma UCB by 30% (each p<0.001). Dose–response experiments showed a strong, linear relation between the gastrointestinal transit time and plasma UCB concentrations (r=0.87, p<0.001). Conclusion: Gastrointestinal transit time and plasma UCB concentrations are linearly related in Gunn rats. This relationship can be exploited by pharmacologically accelerating the gastrointestinal transit, which increases transmucosal UCB diffusion and thereby effectively treats unconjugated hyperbilirubinaemia. Present results support the feasibility of PEG treatment, either solitary or combined with phototherapy, in patients with severe unconjugated hyperbilirubinaemia.